Expression analysis of the Arabidopsis CP12 gene family suggests novel roles for these proteins in roots and floral tissues - Singh, Prashant (Journal of experimental botany, 2008)
The chloroplast protein CP12 has been shown to regulate the activity of two Calvin cycle enzymes, phosphoribulokinase (PRK) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH), by the reversible formation of a multiprotein complex. In Arabidopsis there are three CP12 genes, CP12-1, CP12-2, and CP12-3, and expression analysis suggested that the function of these proteins may not be restricted to the Calvin cycle. Reverse transcription-PCR analysis was used here to investigate further the expression patterns of the three CP12 Arabidopsis genes together with the genes encoding plastid GAPDH (GAPA-1 and GAPB), PRK (PRK), and plastid NAD-dependent GAPDH (GAPCp1 and GAPCp2) during development, in response to changes in light, temperature, and anaerobic conditions. Expression of the CP12-2 gene was similar to that of the Calvin cycle enzymes PRK and GAPDH. However, this was not the case for CP12-1 and -3 which were both expressed in roots. Analysis of transgenic Arabidopsis lines expressing CP12::GUS fusion constructs revealed that the CP12 genes display different spatiotemporal expression patterns. The CP12-1 gene was expressed in root tips whilst CP12-3::GUS expression was evident throughout the root tissue. The most unexpected finding was that all three CP12 genes were expressed in floral tissues; CP12-1 and CP12-2 expression was detected in the sepals and the style of the flower, while in contrast CP12-3::GUS expression was restricted to the stigma and anthers. Taken together, the data suggest that the redox-sensitive CP12 proteins may have a wider role in non-photosynthetic plastids, throughout the plant life cycle